Mechanical properties, dynamic mechanical analysis and molecular cross-linking of GTR/NR re-Vulcanized blends. Issue 4 (November 2022) - Zitzumbo, R; Alonso, S; Estrada-Monje, A; Becerra, María B; Avalos, F; Medina-Torres, L
The effect of natural rubber (NR) on mechanical, chemical and thermal properties of ground tire rubber (GTR) was investigated. Mechanical and thermal properties of GTR/NR vulcanized blends were determined with a universal testing machine and a dynamic mechanical analyzer (DMA). The molecular cross-linking density was determined by molecular swelling in toluene. Presents results indicate that the carbon black embedded in the GTR interior phase of the GTR/NR re-vulcanized blends, did not participate in the NR phase molecular motion restriction. The blends of GTR/NR showed the phenomenon known as reversion, leading a decreasing of the mechanical properties, that could be attributed of the degradation of the interphases (GTR/NR)n+j, j=1, 2, 3, … . On the other hand, the Cole-Cole charts of the GTR/NR vulcanized blends changed from a semicircular to an irregular form as the NR concentration increases, imposing the heterogeneity of the blend. In addition, in the Cole-Cole charts of GTR/NR vulcanized and re-vulcanized blends, the height ( E´´ ) and the width ( E´ ) of the curves decreased while the re-vulcanization processes number was greater; obtained results could be attributed to the increasing of the molecular cross-linking density.